1992
DOI: 10.1620/tjem.167.247
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Investigations of Placental Terminal Villi in Maternal Diabetes Mellitus by Scanning and Transmission Electron Microscopy.

Abstract: The structure of the terminal villi was observed in placentae from non-diabetic mothers and mothers with diabetes mellitus using scanning and transmission electron microscopy. The metabolic condition of maternal diabetes was tightly controlled. In the diabetic group, the diameter of the terminal villi was significantly smaller than in the control group. The ramification pattern of villi, classified into hypo-, moderate-and hyper-ramifications, was shown to be mostly moderate in the non-diabetics whereas most o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…The placentae of diabetic rats displayed significant cell hyperplasia and thickening of the basal membrane of syncytial cells, while these could not be observed in the placentae of rats in the control group. Cytotrophoblastic cell prolifera- tion is accepted as an indicator of uteroplacental ischemia, as reported in other studies (10). In this study, we observed an increase in embryonic loss, a decrease in the number of living fetuses, and a lower rate of implantation in diabetic rats.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The placentae of diabetic rats displayed significant cell hyperplasia and thickening of the basal membrane of syncytial cells, while these could not be observed in the placentae of rats in the control group. Cytotrophoblastic cell prolifera- tion is accepted as an indicator of uteroplacental ischemia, as reported in other studies (10). In this study, we observed an increase in embryonic loss, a decrease in the number of living fetuses, and a lower rate of implantation in diabetic rats.…”
Section: Discussionsupporting
confidence: 86%
“…This basal membrane thickening could be the result of mucopolysaccharide storage (19), which results in maternal uteroplacental vascular insufficiency and intrauterine growth retardation (1). In addition, we also observed thickening of the capillary basal membrane of diabetic rat placentae, which leads to an increased diffusion distance between maternal and fetal blood (10).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Oxidative stress is enhanced in pregnancies complicated by insulindependent diabetes (8, 9), toxemia (5, 6, 10-13) and cigarette smoking (39). In many of these cases a structurally abnormal, small or poorly functioning placenta is found (40)(41)(42)(43)(44)(45). In some diabetic placentas, obliterative endarteritis of fetal stem cells and villous fibrinoid necrosis are observed (42).…”
Section: Discussionmentioning
confidence: 99%
“…occurrence of shorter villi in the centre and longer villi in periphery, is disrupted, and villi (and villous vessels, as deduced by authors) are more branched in diabetic placentas (Bjork & Persson, 1984). The analysis performed by scanning electron microscopy revealed hypo-and hyperramified villi in diabetic placentas as compared with normal ones (Honda et al, 1992).…”
Section: Light Microscopymentioning
confidence: 89%